Maritime Diplomacy in Realizing the Vision of Golden Indonesia 2045 through the Concept of World Maritime Axis - Dao, Yunias (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
Indonesia plays an important role in global maritime dynamics. The maritime sector is critical to international trade and regional security. The concept of the World Maritime Axis has been introduced as the basis for Indonesia's maritime development. The Golden Indonesia Vision 2045 is Indonesia's long-term roadmap to become a major economic power. It focuses on the optimal use of the maritime sector, with maritime diplomacy playing an important role in achieving this vision. This article examines the research objectives to answer the main question: "How do the projections and strategies of maritime diplomacy contribute to the achievement of Indonesia's Golden Vision 2045 through the World Maritime Axis Concept?". This study uses a qualitative approach to examine the projected achievement of the Golden Indonesia Vision 2045 through the concept of the World Maritime Axis. The data collection technique is a comprehensive literature review, including government policy documents, international reports, and relevant academic publications. Data analysis was conducted using content analysis techniques to identify, analyze and report patterns (themes) in the data. The research findings show that Indonesia must navigate shifts in global power competition. Indonesia's maritime diplomacy will play an important role in optimizing maritime resources for national and international interests. To strengthen these efforts, a strong defense and security posture is needed amidst regional dynamics.